A Near-Lossless Image Compression Algorithm Suitable for Hardware Design in Wireless Endoscopy System. (24th September 2006) - Xie Xie, Xiang Xiang; Li Li, GuoLin GuoLin; Wang Wang, ZhiHua ZhiHua
Abstract : In order to decrease the communication bandwidth and save the transmitting power in the wireless endoscopy capsule, this paper presents a new near-lossless image compression algorithm based on the Bayer format image suitable for hardware design. This algorithm can provide low average compression rate (2.12 bits/pixel) with high image quality (larger than53.11 dB) for endoscopic images. Especially, it has low complexity hardware overhead (only two line buffers) and supports real-time compressing. In addition, the algorithm can provide lossless compression for the region of interest (ROI) and high-quality compression for other regions. The ROI can be selected arbitrarily by varying ROI parameters. In addition, the VLSI architecture of this compression algorithm is also given out. Its hardware design has been implemented in0.18 μ m CMOS process.